Gut microbiome and gastric cancer: microbial interactions and therapeutic potential - Maged Tharwat Elghannam; Moataz Hassan Hassanien; Yosry Abdelrahman Ameen; Emad Abdelwahab Turky; Gamal Mohammed ELattar; Ahmed Aly ELRay; Mohammed Darwish ELTalkawy (Gut Pathogens)
Abstract The development of gastric cancer is significantly influenced by the intestinal microbiota, with H. pylori serving as a major risk factor. Through genotoxic effects, persistent inflammation, and metabolic changes, other microbes also play a role. It has been demonstrated that cancer patients and healthy people have different microbiome compositions. Cancer can be inhibited or promoted by the gut microbiota and its metabolites. The relationship between intestinal flora, bacterial extracellular vesicles, and the tumor microenvironment directly affects tumor progression and efficacy of anti-tumor medications, indicating the importance of the tumor microenvironment in tumor survival. Gastrointestinal malignancies may be brought on by the gut microbiome’s dysregulation of non-coding RNA expression. Non-coding RNAs are intriguing avenues for future therapeutic and diagnostic research. The tumor microenvironment is altered by bacterial extracellular vesicles, which may have an effect on immunosuppression, treatment resistance, metastasis, and cancer progression. Further research is required to completely understand the involvement of non-coding RNAs in GI cancers. By modifying drug metabolism and absorption, which have a substantial impact on healing efficacy and serious impact profiles, the dynamic changes in gut microbiota also have a considerable impact on the results of anti-cancer treatment. Improved treatment approaches may arise from a better understanding of the role of the microbiome in gastric malignancies.